How hard is the euro area core? An evaluation of growth cycles using wavelet analysis - Patrick M. Crowley; Douglas Maraun; David Mayes (Bank of Finland, 2006)
Using recent advances in time-varying spectral methods, this research analyses the growth cycles of the core of the euro area in terms of frequency content and phasing of cycles.The methodology uses the continuous wavelet transform (CWT) and also Hilbert wavelet pairs in the setting of a non-decimated discrete wavelet transform in order to analyse bivariate time series in terms of conventional frequency domain measures from spectral analysis.The findings are that coherence and phasing between the three core members of the euro area (France, Germany and Italy) have increased since the launch of the euro.
URN:NBN:fi:bof-20140807353
Keywords: C19; C63; C65; E32; E39; E58; F40; 330; time-varying spectral analysis; coherence; phase; business cycles; EMU; growth cycles; Hilbert transform; wavelet analysis